Dietary self-control influences top–down guidance of attention to food cues - Higgs, Suzanne; Dolmans, Dirk; Humphreys, Glyn W.; Rutters, Femke (Frontiers in Psychology, 2015)
Motivational objects attract attention due to their rewarding properties, but less is known about the role that top-down cognitive processes play in the attention paid to motivationally relevant objects and how this is affected by relevant behaviour traits. Here we assess how thinking about food affects attentional guidance to food items and how this is modulated by traits relating to dietary self-control. Participants completed two tasks in which they were presented with an initial cue (food or non-food) to either hold in working memory (memory task) or to merely attend to (priming task). Holding food items in working memory strongly affected attention when the memorized cue re-appeared in the search display. Tendency towards disinhibited eating was associated with greater attention to food versus non-food pictures in both the priming and working memory tasks, consistent with greater attention to food cues per se. Successful dieters, defined as those high in dietary restraint and low in tendency to disinhibition, showed reduced attention to food when holding food-related information in working memory. These data suggest a strong top-down effect of thinking about food on attention to food items and indicate that the suppression of food items in working memory could be a marker of dieting success.